Impact of terminal ileal microbiota dysbiosis and tryptophan metabolism alterations on mental disorders in patients with Crohn’s disease - Yin Lin; Fang-Tao Wang; Kai Xia; Ren-Yuan Gao; Yi-Ran Jiao; Min Fang; Chun-Qiu Chen (BMC Gastroenterology)
Abstract Background Crohn’s disease (CD) is a chronic non-specific inflammatory bowel disease with an increasing incidence worldwide. Patients with CD are facing elevated risk for mental disorders (MD) than healthy people, and chronic psychological stress is considered to trigger deterioration and relapse of CD. The microbiome-gut-brain axis (MGBA) is recognized as a crucial factor in unraveling this connection. Whereas, so far, few studies have revealed the relationship of the microbiota communities and tryptophan catabolites of the terminal ileum mucosa on gut-brain communication. Materials and methods A total of 52 patients with CD, along with 11 patients with colorectal cancers recruited as controls, were enrolled in this study. The participants completed Patient Health Questionnaire-9 and Generalized Anxiety Disorder-7 Questionnaire. The terminal ileal mucosa was collected during surgery. We profiled the microbiota composition of 37 patients and quantified the tryptophan catabolites of 28 patients utilizing 16 S rRNA gene sequencing and liquid chromatography-tandem mass spectrometry, respectively. In addition, bioinformatics methods were used to elucidate the interrelationships between psychological states, microbial communities, and tryptophan catabolites. Results CD patients with MD showed a significant reduction in microbial diversity within the ileal mucosa. Regarding microbial composition, Prevotella was relatively enriched in CD patients with MD, along with lower relative abundances of Akkermansia and Faecalibacterium. Furthermore, significant disparities in the levels of Picolinic acid (PA), Kynurenic acid (KYNA), Nicotinic acid (N-Acid), and Indole-3-carbaldehyde (ICAld) were detected within the ileal mucosa of CD patients comorbid with MD. A pronounced correlation was observed between PA levels and anxiety scale scores. The heightened abundance of Prevotella may be closely associated with altered levels of PA, N-Acid, and KYNA. Conclusion Alterations in the microbial composition of the terminal ileum may interact with changes in tryptophan metabolism and are associated with MD in patients with CD undergoing surgery.